Recent advances in rice varietal development for durable resistance to biotic and abiotic stresses through marker-assisted gene pyramiding - Haque, Md Azadul; Rafii, Mohd Y.; Mohammad Yusoff, Martini; Syd Ali, Nusaibah; Yusuff, Oladosu; Datta, Debi Rani; Anisuzzaman, Mohammad; Ikbal, Mohammad Ferdous (MDPI, 2021)
Abiotic and biotic stresses adversely affect rice growth, development and grain yield. Traditional rice breeding techniques are insufficient in modern agriculture to meet the growing population’s food needs on a long-term basis. The development of DNA markers closely linked to target genes or QTLs on rice chromosomes, and advanced molecular techniques, such as marker-assisted selection (MAS), have encouraged the evolution of contemporary techniques in rice genetics and breeding, such as gene pyramiding. Gene pyramiding refers to the act of combining two or more genes from multiple parents into a single genotype, which allows the overexpression of more than one gene for broad-spectrum abiotic and biotic stress resistance. Marker-assisted pedigree, backcrossing and pseudo-backcrossing methods can increase the conventional breeding speed by reducing the number of breeding generations in order to enhance the pyramiding process. Pyramiding is affected by several factors: the number of transferred genes; the range within gene and flanking markers; the number of chosen populations in every breeding generation; the features of genes and germplasms; and the potentiality of breeders to identify the target genes. Modern breeding methods, such as the marker-assisted backcrossing approach, have made gene pyramiding more precise and reliable for the development of stress-tolerant rice varieties in the coming decades. This review presents up-to-date knowledge on gene pyramiding schemes, marker-assisted gene pyramiding techniques, the efficiency of marker-assisted gene pyramiding and the advantages and limitations of gene pyramiding methods. This review also reports on the potential application of marker-assisted selection breeding to develop stress-tolerant rice varieties that stabilize abiotic and biotic stresses. This review will help rice breeders to improve yields by increasing rice productivity under abiotic and biotic stress conditions.